Synthesis of N-(4-chlorophenyl) substituted pyrano[2, 3-c]pyrazoles enabling PKBβ/AKT2 inhibitory and in vitro anti-glioma activity. (31st December 2022) - Vala, Ruturajsinh M.; Tandon, Vasudha; Nicely, Lynden G.; Guo, Luxia; Gu, Yanlong; Banerjee, Sourav; Patel, Hitendra M.
Abstract: A series of N -(4-chlorophenyl) substituted pyrano[2, 3-c]pyrazoles was synthesised and screened for their potential to inhibit kinases and exhibit anticancer activity against primary patient-derived glioblastoma 2D cells and 3D neurospheres. A collection of 10 compounds was evaluated against glioma cell lines, with compound 4j exhibiting promising glioma growth inhibitory properties. Compound 4j was screened against 139 purified kinases and exhibited low micromolar activity against kinase AKT2/PKBβ. AKT signalling is one of the main oncogenic pathways in glioma and is often targeted for novel therapeutics. Indeed, AKT2 levels correlated with glioma malignancy and poorer patient survival. Compound 4j inhibited the 3D neurosphere formation in primary patient-derived glioma stem cells and exhibited potent EC50 against glioblastoma cell lines. Although exhibiting potency against glioma cells, 4j exhibited significantly less cytotoxicity against non-cancerous cells even at fourfold–fivefold the concentration. Herein we establish a novel biochemical kinase inhibitory function for N -(4-chlorophenyl) substituted pyrano[2, 3-c]pyrazoles and further report their anti-glioma activity in vitro for the first time. KEY MESSAGE: Anti-glioma pyrano[2, 3-c]pyrazole 4j inhibited the 3D neurosphere formation in primary patient-derived glioma stem cells. 4j also displayed PKBβ/AKT2 inhibitory activity. 4j is nontoxic towards non-cancerous cells.